2006
DOI: 10.1152/ajpheart.00945.2005
|View full text |Cite
|
Sign up to set email alerts
|

Connexin40 and connexin43 in mouse aortic endothelium: evidence for coordinated regulation

Abstract: In the vessel wall, endothelial cells are metabolically and electrically coupled to each other and to the adjacent smooth muscle cells by gap junctions composed of connexins. Gap junctions may be formed from combinations of several different connexin proteins, and deletion of one connexin can lead to modification of the expression of another. To reveal a possible interaction between connexin40 (Cx40) and connexin43 (Cx43) in endothelium, we studied their distribution in vessels from C57Bl/6 and Cx40 knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 36 publications
3
64
1
Order By: Relevance
“…In the homozygous Cx40 knock-out mouse, deletion of Cx40 in the endothelium was accompanied by reduction of Cx43 protein expression [20]. It was shown that contrary to this study, deletion of one connexin in myocardium of transgenic mice was not accompanied by a compensatory change in expression of another connexin [18].…”
Section: Cell Morphologycontrasting
confidence: 96%
See 1 more Smart Citation
“…In the homozygous Cx40 knock-out mouse, deletion of Cx40 in the endothelium was accompanied by reduction of Cx43 protein expression [20]. It was shown that contrary to this study, deletion of one connexin in myocardium of transgenic mice was not accompanied by a compensatory change in expression of another connexin [18].…”
Section: Cell Morphologycontrasting
confidence: 96%
“…Evidence for transregulation of connexin expression has been reported [20]. In the homozygous Cx40 knock-out mouse, deletion of Cx40 in the endothelium was accompanied by reduction of Cx43 protein expression [20].…”
Section: Cell Morphologymentioning
confidence: 99%
“…Both sequences contain conserved motifs that are involved in connexin-connexin interaction in gap junction channels (Dahl et al, 1992;Warner et al, 1995). These motifs are not consistently found in other cell surface proteins suggesting that Gap26 and Gap 27 specifically interact with Cx43 without interfering with other Cx or surface proteins (Braet et al, 2003a;Isakson et al, 2006;Warner et al, 1995). In fact, the selective affinity of Gap26 and Gap27 toward Cx43Hc was first reported in 2003 by Braet and collaborators (Braet et al, 2003a;Braet et al, 2003b).…”
Section: Structural Cx-mimetic Peptides As Inhibitors Of Cxhc Functionmentioning
confidence: 99%
“…For immunoblot analysis, the vascular cell cocultures were snap-frozen with liquid nitrogen, and EC and VSMC were removed with Laemmli sample buffer (Bio-Rad) and run on a 12.5% SDS-PAGE. Antibodies used for identification of connexins have previously been shown to be specific 17,22 and include anti-Cx37 (ADI; Zymed), anti-Cx40 (ADI; Zymed), anti-Cx43 (Sigma [intracellular loop for immunoblot; C-terminal tail for immunohistochemistry]), and anti-tyrosine 265-specific Cx43 (Santa Cruz Biotechnology). Antibodies raised against Cx45 were not considered specific (eg, Theis et al 23 ).…”
Section: Immunocytochemistry/immunoblotmentioning
confidence: 99%
“…This is in contrast to connexin expression levels in EC (ie, lacking inflammatory stimuli), which have been demonstrated previously to have coregulated connexins, ie, the up or down connexin expression is dependent on the expression of other connexins. 22,28,29 How OxPAPC may decouple connexin coregulation is potentially of great interest in understanding EC response to inflammatory mediators. As the effects of OxPAPC on nuclear transcription factors become more clear (eg, Kronke et al 24 ), a more precise idea of the differential control of connexin expression will likely become more evident.…”
Section: Summary Of Changes In Connexin Expressionmentioning
confidence: 99%